Tinjauan Historitas Simbol Harmonisasi Antaretnis Tionghoa dan Melayu di Bangka Belitung - Meta Sya; Rustono Farady Marta; Teguh Priyo Sadono (Jurnal Sejarah Citra Lekha, 2019)
This article discusses the historical background of the formation of the Bangka Belitung islands as a province full of harmonization symbols, namely ethnic Chinese and Malays (Thongin Fangin Jit Jong). Based on historical searches using primary and secondary sources, it can be concluded that the arrival of the Chinese in Bangka as miners has made a mixture of Chinese and Malay ethnic groups in Bangka. Then, the assimilation was expressed with an attitude of solidarity between the two, which began with the arrival of the white nation in Bangka, causing a resistance between ethnic Chinese and Malays through the Bangka War led by Depati Amir. This was done because of the feelings of oppression and suffering experienced by ethnic Chinese and Malays at that time. Then, the attitude of solidarity did not stop at that moment, but when Bangka Belitung struggled to break away from South Sumatra. The participation of the entire community of the Bangka Belitung Islands together struggled to be able to provide prosperity. Therefore, historical ties become very important media in the formation of the symbol of harmonization.